Antibacterial Effectiveness Test of Lemongrass Leaf Extract (Cymbopogon citratus) on the Growth of Streptococcus sanguinis on Removable Orthodontic Acrylic Bases - Davin Davin; Cindy Denhara Wijaya; Nora Fine Damayanti Sianipar (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2026)
The use of acrylic base as a removable orthodontic base plate has the disadvantage of being porous, thus increasing the risk of microorganism colonization, including Streptococcus sanguinis. Lemongrass leaves (Cymbopogon citratus L.) contain secondary metabolites that have antibacterial properties such as alkaloids, saponins, tannins, polyphenols. The purpose of this study was to determine the antibacterial effectiveness of lemongrass leaf extract (Cymbopogon citratus) 40% and 50% against the growth of Streptococcus sanguinis on removable orthodontic acrylic bases. This type of research is a true experimental with a post- test only control group design. The number of groups in this study was 4 (four), each consisting of 6 replications. The antibacterial testing of lemongrass leaf extract used the diffusion method. Data analysis used the Kruskal-Wallis and Mann-Whitney statistical tests. Based on the results of the study, the average number of Streptococcus sanguinis bacterial colonies on removable orthodontic acrylic bases from negative controls, positive controls, 50% and 40% lemongrass leaf extract was 1725±171,980 CFU/mL, 4.17±2,639 CFU/mL, 451.67±57,840CFU/mL, and 662.50±23,889 CFU/mL. The results of the Kruskal-Wallis test stated that there was a significant difference in the average number of colonies between all groups (p=0.000; p<0.05). The results of the Mann-Whitney test stated that there was a significant difference in antibacterial effectiveness between the two different groups (p=0.004; p<0.05). The conclusion of this study is that lemongrass leaf extract has antibacterial effectiveness against the growth of Streptococcus sanguinis on removable orthodontic acrylic bases